Use of endoscopy to determine the resection margin during laparoscopic gastrectomy for cancer. Issue 13 (11th September 2017) - Kawakatsu, S.; Ohashi, M.; Hiki, N.; Nunobe, S.; Nagino, M.; Sano, T.
Abstract : Background: It can be difficult to determine the transection line during totally laparoscopic surgery for early gastric cancer owing to lack of tactile feedback. This retrospective cohort study aimed to assess the role of intraoperative endoscopy in determining the resection margin in totally laparoscopic gastrectomy. Methods: Consecutive patients with histologically confirmed gastric cancer who underwent laparoscopic gastrectomy between March 2012 and July 2015 were eligible. Preoperative placement of marking clips and intraoperative endoscopy were performed to determine the resection margin. Frozen‐section analyses were also performed to confirm the absence of cancer cells at the surgical margin. Success was defined as the proportion of specimens with all clips present and by the proportion of resections with a negative surgical margin following initial transection. Results: Total laparoscopic gastrectomy with intraoperative endoscopy was performed in 522 patients; a total of 662 surgical margins were analysed. The overall success rate was 99·8 per cent (661 of 662 margins). The success rate of achieving a negative surgical margin during the initial transection was 98·9 per cent (550 of 556 margins). Conclusion: Preoperative placement of marking clips and intraoperative endoscopy is helpful in the determination of a safe surgical margin in patients with gastric cancer who undergo laparoscopic gastrectomy. Abstract : Helpful